Success Rate of Glaucoma Drainage Device Implantation in Kariadi General Hospital Semarang 2020-2022: Oral Presentation - Observational Study - Resident - Maharani; Apriliana, Rina; Rachmi, Fifin L; Puspasari, Denti (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesGlaucoma is a leading cause of irreversible blindness, and implantation of drainage devices is aneffective treatment option for patients with advanced glaucoma. The purpose of this study was toinvestigate success rate of glaucoma drainage devices implantation in Kariadi Hospital MethodsThis study was an observational analytic study with a retrospective design. All patients who receivedVirna implantation between January 2020 and December 2022 were included. Intraocular pressure(IOP) examination was performed at baseline and at the first day, seventh day, first month, and thirdmonth following surgery. The success rate was divided into three groups: complete success if IOPwas <21mmHg without medication, qualified success if IOP was <21mmHg with medication, andfailure if IOP was >21mmHg with medication. ResultsThis study included 42 patients (42 eyes) with an average age of 43.3 years. There were 16 male(38%) and 26 female (62%) patients in the group. Of these patients, 11 (26.2%) had primaryglaucoma and 31 (73.8%) had secondary glaucoma. There was significant decrease in IOP frompreoperative measurement (37.1±10.1mmHg) compared to IOP on first day (13.0±6.0mmHg),seventh day (15.4±3.8mmHg), first month (18.2±4.4mmHg), and third month (23.4±8.9mmHg) aftersurgery (p<0.05). At three-month follow-up, complete success was 14.29%, qualified success was50%, and failure was 35.71%. ConclusionGlaucoma drainage device implantation was found to successfully reduce IOP in patients withadvanced glaucoma. The qualified success rate was higher than complete success rate, suggestingthat some patients may require medication to achieve target IOP levels.